Sensitivity of Signal-to-Noise Ratio to the Layer Profile and Crystal Quality of SiGe/Si Multilayers. (24th February 2016) - Radamson, H. H.; Moeen, M.; Abedin, A.; Hojabri, A.; Salemi, A.; Kolahdouz, M.
Abstract : This study presents signal-to-noise ratio (SNR) measurements of single crystalline dots or layers of SiGe/Si in multilayer structures in terms of Ge content, interfacial and layer quality. All multilayers were processed in form of mesas and the noise behavior of electrical signal was investigated by comparing the power spectral density curves and K1/f values. The SiGe/Si multilayer structures were also characterized by the conventional material analysis tools and the results were compared to the noise measurements. The quality of SiGe/Si interface or SiGe layer was monitored by intentional exposure to oxygen in range of 2–1600 nTorr either during or prior to SiGe growth. The results demonstrated that SNR was sensitive to the interfacial and layer quality, and the Ge content in a multilayer structure. The noise level became very high when the strain fluctuated within SiGe layer and this occurred for SiGe with high Ge content or SiGe dots.